The secret life of bees - Kidd, Sue Monk. (New York : Penguin, 2003)
Now in paperback comes the intoxicating debut novel of "one motherless daughter's discover of ... the strange and wondrous places we find love" ("The Washington Post"). Sue Monk Kidd's ravishing work is set in South Carolina in 1964.
Includes "A Penguin readers guide to The secret life of bees."
Keywords: Teenage girls -- Fiction; African American women -- Fiction; Maternal deprivation -- Fiction; South Carolina -- Fiction; Race relations -- Fiction; Beekeepers -- Fiction; Sisters -- Fiction; Bildungsromans; Domestic fiction